O Folclórico e o político no teatro de yeats: estética romântica e nacionalismo em The countess cathleen - Vieira, Bruno Rafael de Lima (2015)
Heavy chains had been keeping Ireland attached to the English colonial system. During seven hundred years, Ireland had been fighting for its political, military, financial and religious independence. The nationalists, arising from the process of seeking for sovereignty, had idealized on the historical roots and on the necessary weaponry for their national project to succeed. This path, nonetheless, pervaded the Celts, the people that became the nation’s spirit for the national movement. Thus, the myths, tales and ancient Gaulish folk tales were freshend. Literature became one of the most important pillars for Ireland’s independence enterprise. William Butler Yeats (1865-1939) founds the Celtic Twilight characterized by a group that started, in short, the presentation of the Irish people, by emphasizing to the Celtic inheritance over culture though drama. By this time, Yeats writes The Countess Cathleen, a play that opens both Celtic Twilight and Abbey Theater, in Ireland. The plot presents the conflicts of a community devasted by starvation. It spins around a heroic character, Countless Cathleen, the action evolves with the appeal for the nationalist sacrifice. By offering her soul towards the country people, Cathleen evokes pagan and Christian myths, in a plot that inspires historical facts and political ideals. In this scenario, our work has for its purpose to investigate the building of Cathleen as an Irish heroin, and the folkloric tales used by Yeats during this learning process of this main character for the play, during the action. For this, we turn to theorists like Propp (1984), Sperber (2009), Campbell (2007), Bettelheim (2012). Due to the Romantic aesthetics overlaid Yeat’s plot, we also had to carry a historical and theoretical analysis on Romantic movement main aspects, especially the movement that brought to life medieval feelings through the Medieval Revival during the nineteenth century. The analysis is built as symbolic and allegorical literature reflecting , respectively , the engagement of the work to the Celtic folklore and the political purpose of the nationalist struggle waged by Yeats